2015
DOI: 10.1007/s11661-015-3144-5
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior, Deformation Mechanisms, and Creep Life of Mod.9Cr-1Mo Steel

Abstract: The creep behavior, deformation mechanisms, and the correlation between creep deformation parameters and creep life have been investigated for Mod.9Cr-1Mo steel (Gr.91, 9Cr-1Mo-VNb) by analyzing creep strain data at 723 K to 998 K (450°C to 725°C), 40 to 450 MPa, and t r = 11.4 to 68,755 hours in NIMS Creep Data Sheet. The time to rupture t r is reasonably correlated with the minimum creep rate _ e min and the acceleration of creep rate by strain in the acceleration region dln_ e/de, as t r = 1.5/[_ e min (dln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 41 publications
8
36
1
Order By: Relevance
“…This change was considered to be caused by the occurrence of homogeneous recovery in the elastoplastic creep in the short term and heterogeneous recovery in the elastic creep in the long term just as the creep strength abruptly decreased in the long term (Kimura, 2004). This change in the inclination of the Monkman-Grant plot was also reported by Abe (Abe, 2015). Therefore, the creep strain equation of Mod.9Cr-1Mo steel should be improved considering the changes in creep characteristics at high temperatures in the long term.…”
Section: Mod9cr-1mo Steel 31 Database Of Mod9cr-1mo Steelsupporting
confidence: 55%
“…This change was considered to be caused by the occurrence of homogeneous recovery in the elastoplastic creep in the short term and heterogeneous recovery in the elastic creep in the long term just as the creep strength abruptly decreased in the long term (Kimura, 2004). This change in the inclination of the Monkman-Grant plot was also reported by Abe (Abe, 2015). Therefore, the creep strain equation of Mod.9Cr-1Mo steel should be improved considering the changes in creep characteristics at high temperatures in the long term.…”
Section: Mod9cr-1mo Steel 31 Database Of Mod9cr-1mo Steelsupporting
confidence: 55%
“…1,[3][4][5][6][7][8][9] The acceleration of tertiary creep due to extensive migration of low-angle boundaries is considered to be the main reason for the creep strength breakdown, i.e., a sudden drop of the allowed stress in the range of long-term creep. 1,[4][5][6]13) In general, the evolution of TMLS during creep have been addressed in several studies. 3,10,14,15) However, limited attention was paid to the evolution of lath boundaries with strain.…”
Section: Evolution Of Lath Substructure and Internal Stresses In A 9%mentioning
confidence: 99%
“…2(c)) that is indicative of the significantly slow processes at tertiary creep. 4,13,[22][23][24] The stress dependence of minimum strain rate is commonly expressed by a power law relationship of applied stress, σ :…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, these studies confirmed the above-mentioned trends and indicated qualitatively similar behaviors for all ferritic-martensitic steel grades. However, the number of studies dealing with fatigue and creep-fatigue of these materials is still quite limited, compared to the great efforts spent on characterizing the creep behavior [12], especially when considering the large parameter fields which would need to be covered for a thorough analysis of the material behavior, under the different combined loadings. Consequently, the amount of available fatigue data is quite restricted, as is reflected, for example, in the number of creep data and fatigue data sheets provided by NIMS in Japan [13].Recently, combined loading involving creep and cyclic fatigue loads has received increased attention due to the more flexible operation of power plants in many countries.…”
mentioning
confidence: 99%